Digital Diaspora, Social Memory, and Resistance: The Construction of Turkish Diasporic Identity in Germany - Salih Tiryaki; Rahma M. K. Mohammed (Contemporary Review of the Middle East, 2026)
This study uses a netnographic approach to explore identity and belonging within the Turkish digital diaspora in Germany, focusing on the DiasporaTürk X account. It shows that digital platforms serve as spaces for cultural expression, collective memory, solidarity, and resistance. The analysis reveals that diasporic identity is fluid and negotiated through transnational interactions, forming a hybrid sense of belonging between Türkiye and Germany. Five core themes emerged: (a) Migration and Diaspora Formation, centering on first-generation narratives and community building; (b) Cultural Adaptation, Difference, and Humor, reflecting identity negotiation and humor as a coping tool; (c) Racism, Violence, and Trauma, focusing on shared digital memory and discrimination; (d) Memory and Resistance, highlighting digital activism; and (e) Cultural Representation and Musical Resistance, showing music’s role in diasporic expression. The study emphasizes the transformative power of digital media in constructing diasporic identities and reveals the layered, dynamic nature of digital diaspora practices.